Hepatomegaly, weight loss and general malaise – the first manifestations of primary systemic amyloidosis - Cichoż-Lach, Halina; Prozorow-Król, Beata; Swatek, Jarosław; Skrzydło-Radomańska, Barbara; Buk, Leszek; Zdunek, Małgorzata; Kowalik, Agnieszka; Słomka, Maria (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Amyloidosis is characterised by the accumulation of poorly soluble fibrous proteins in the extracellular space of various bodily organs. Light chain amyloidosis (AL) is recognised as the most common form of systemic amyloidosis. Light chains are deposited in the majority of bodily organs, and accumulation of them in the liver produces hepatomegaly. We report a case of AL-systemic amyloidosis with liver involvement in a 71-year-old woman. Hepatomegaly, weight loss and general malaise were the first manifestations of the disease. Liver biopsy found amyloid deposits along the sinusoids as well as in the space of Disse, inside the vascular wall and in connective tissue of the portal tracts, which showed a positive reaction in Congo Red stain. Further diagnosis showed the presence of systemic amyloidosis. The patient was put on cyclophosphamide and steroid therapy.